Sins of the Father: Exploring Shame as an Ethical Pedagogy to Advance British Columbia’s K–12 Settler Students Towards Reconciliation - Brar, Victor (Philosophical Inquiry in Education, 2024)
This paper reflects my journey, as a racialized settler and K–12 practitioner in British Columbia, Canada, towards developing a pedagogical understanding of how to transform the experience of inherited colonial shame among settler children in my classroom. Canada has a shameful history of colonialism, the progressive revelations of which provoke an iterative cycle of shame among many of the children in our schools. This cycle prevents these children from emerging as responsible agents of reconciliation. I examine the hidden pedagogical potential of shame to function as an ethical catalyst for reconciliatory change. I posit that Aristotle’s conception of shame (aidos), when paired with Freire’s (1970) critical pedagogy, can provide the means to energize my pedagogical efforts to address the shame of settler students and enable them to pursue respectful mutual relationships with Indigenous Peoples in Canada. By fusing the philosophical horizons of Aristotelian shame with Freire’s critical pedagogy, I argue that the future for settler children need not appear as a fait accompli, in which the “sins of father” will be visited upon the children of another generation.